Deluxe : how luxury lost its lustre - Thomas, Dana (Penguin, 2008)
What is the new definition of luxury when the advertising for the luxury life is targeted mainly towards the middle-classes? What are we paying for when quality is no longer quality? Dana Thomas delves into the real world behind glossy spreads in magazines and fantastic dresses on the red carpet.